A. I. and Remote Working : A Paradigm Shift in Employment. - Miller, Tony. (New York : Business Expert Press, 2021)
This innovative book will guide you through A.I., how it will affect employment and existing processes, and what the employer and employee can expect in the new and rapidly changing world of work.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Chapter 1: What Is Artificial Intelligence and Remote Working? What Is Its Impact Going to Be? -- Chapter 2: Human Resources-On the Front Line for a Change -- Chapter 3: How AI, Homeworking, and Process Redesign Will Impact on Organizational Structures and Reducing Headcount-Rightsizing Your Organization -- Chapter 4: Aligning HR Processes with AI-Productivity Measurement and Performance Appraisal -- Chapter 5: Automating Training Needs Analysis and Training Evaluation -- Chapter 6: Digital Footprints and How They Can be Used to Upgrade Recruitment and Succession Planning-The End of Testing? -- Chapter 7: Pay and Rewards -- Chapter 8: New Skills Needed to Manage This Massive Paradigm Shift from Traditional HR To Artificial Intelligence Focused HR -- Chapter 9: Useful Formula and the Productivity Dashboard -- References -- Suggested Readings -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Artificial intelligence; Flexible work arrangements; Telecommuting; Electronic books